COMPREHENSIVE ANALYSIS OF BROUGHT IN DEAD CASES: A RETROSPECTIVE OBSERVATIONAL STUDY IN A TERTIARY HOSPITAL IN NORTH-EASTERN NIGERIA - Chiwar, Hassan Musa; Zarami, Abba Bukar; Agyigra, Aksavdwa Isaac; Ngadda, Haruna Asura; Pindiga, Umaru Hamidu; Bulama, Hayatu Umar; Ahmed, Modu (Journal of Biomedical Investigation, 2023)
Introduction: The Accident and Emergency unit is often the main entry point to hospitals for unexpected diseases, even though no medical care can be provided to Brought In Dead (BID) cases upon arrival. However, valuable information can be deduced from forensic investigations and analysis. Despite a life expectancy of 53 years and civil unrest in North-Eastern Nigeria, there is a lack of studies on BID in the region. Aims: This research aimed to evaluate the frequency, age, and sex distribution, as well as clinical conditions associated with BID cases at the University of Maiduguri Teaching Hospital. Materials and Methods: This retrospective observational study was conducted in the Accident and Emergency Unit of the University of Maiduguri Teaching Hospital, Maiduguri, Borno State, Nigeria. Ethical approval was obtained, and data collection included all BID cases registered between January 2018 and December 2020. The data was summarized using frequency and percentages. Results: Out of 955 deaths recorded during the study period, 204 cases (21.3%) were BID. The BID cases consisted of 136 males (66.7%) and 68 females (33.3%), with a male-to-female ratio of 2:1. The age range of BID cases varied from 0-18 to above 75 years, with the highest frequency observed in the age range of 38-56 years. The most common known clinical conditions associated with BID cases were bleeding from gunshot, cardiopulmonary arrest, chronic kidney disease, and severe malaria. Male BID cases were commonly associated with cardiopulmonary arrest, while female BID cases were associated with cancer. Conclusion: This study provided valuable insights into BID cases at the University of Maiduguri Teaching Hospital. The findings can guide strategies to mitigate BID occurrences and improve health-seeking behavior, especially among young adults.